Analytic hierarchy process and knowledge-based system integration for web-based ergonomics assessment approach in prioritizing workplace critical risk factors - Fazilah, Abdul Aziz (2021)
Conducting workplace ergonomics risk assessment is a legal obligation for all workplaces, including automotive manufacturing plant. The needs for a competent ergonomist to study, design, and evaluate human work system is crucial. Thus, utilizing the technology of knowledge-based system (KBS) in ergonomics makes it possible for an ordinary worker to use ergonomic experts' expertise to accomplish their work accurately and efficiently without experts' assistance. This thesis presents a web-based ergonomics assessment system (W-BEAS) to evaluate and prioritize automotive workplace risks. The study's methodology under phase 1 starts with investigating dominant ergonomics risk factors in the workplace. In the preliminary study, 97 questionnaires were collected out of 120 sets to identify workplace ergonomics' performance, and the improvements demand at an automotive production plant. Under phase 1, the study continues with several methods: MSD symptom investigation, job task assessment, established studies review, domain expert knowledge analysis, and risk factors validation. Then, this study continued with establishing the analytical hierarchy process (AHP) based assessment method for prioritizing the critical ergonomic risk factors. Finally, a web-based ergonomics assessment system (W-BEAS) was developed by integrating the AHP technique, KBS, and web-based approach to evaluate automotive workplace hazards elements. The W-BEAS was developed using XAMMP software by integrating a KBS, the AHP technique and a web server that users can access from any device with an internet connection. Apache's XAMPP software is a cross-platform web-server solution stack that is free and open-source. The preliminary study results showed that about 70% of the respondents observed that employees frequently complained about their job task, and 60% or more of the respondents understood a need to improve their workplace. The investigation process for ergonomics risk factors has produced 26 dominant risk factors stored as knowledge-based for W-BEAS databased. The AHP-based evaluation method identified the organizational ergonomics are the most critical factor that leads to WMSD development in the vehicle component manufacturing plant. The critical sub-risk factors, including the level of education, physical demand at work, force exertion in job task, hand-arm vibration and low job support. The AHP-based evaluation method has validated by the consistency judgement (CR < 0.1). Different assessor groups also have shown similar first-place prioritization value, and the difference is slightly (< 0.05). Thus, the AHP-based evaluation method framework proved practical in prioritizing critical risk factors for workplace ergonomic intervention. W-BEAS applied and produced results that organisational ergonomics is the most critical and individual ergonomics is the less critical risk factor. Meanwhile, W-BEAS validation results showed that the first-place rank of risk factor produced by the W-BEAS and RPN method is comparable. W-BEAS also validated by showing the same prioritizations risk factors produced by both assessor groups. Moreover, both company users were satisfied with the W-BEAS content and system (p > 0.05). The W-BEAS's ability to assess workplace ergonomics risk factors is recognized, and ordinary workers could assess their workplace situations using the website. Therefore, W-BEAS is significant in the automotive industry that allows ergonomics risk information to be accessed and studied at the earliest stages of product and process design.